Strategies Used to Translate Idiomatic Expressions in 'A Walk to Remember' into Indonesian and The Resulted Equivalence - Angguntur, Wayan; Hartono, Rudi; Purwanto, Bambang (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2020)
This study is conducted to analyze the translation strategies used to translate the idiomatic expressions in the novel Ã¢â‚¬Å“A Walk to RememberÃ¢â‚¬Â into Indonesian, to analyze the degree of equivalence of the Indonesian translation, and to find out the relation between the strategy used and the degree of equivalence. The translation strategies used in this study are proposed by Baker while the degrees of equivalence are analyzed by using BellÃ¢â‚¬â„¢s theory. This research belongs to descriptive research using qualitative method to describe the objectives of this study. The data are analyzed by comparing the idioms in the English version to the Indonesian translation. After the data are identified, they are examined to find out the relation between the strategies used and the degree of equivalence. The findings of the analysis are: (1) four strategies were used to translate idioms in the novel A Walk to Remember into Indonesian, (2) in terms of degree of equivalence, it was found that most of the data were identified into fully equivalent translation, (3) in the relation between translation strategies used and the degree of equivalence, it was revealed that the translation strategies used mostly produce fully equivalent with complete meaning. Keywords: a walk to remember, degree of meaning equivalance, idioms translation strategies